Quality Of Work Life and Clinical Competence Towards Patient Safety Culture With Work Motivation Intervening - M Lutfi Dayan Janwar; Aprillita Rina Yanti; Rian Adi Pamungkas (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
This study is based on the results of initial observations that inform that there will be an increase in patient safety incidents in 2023 compared to 2022. The purpose of this study is to empirically reveal the influence of quality of work life and clinical competence on patient safety culture with work motivation as an intervening variable. The type of research is included in the quantitative with a cross sectional study design. The population used is nurses on duty in inpatient installations. The sampling technique used a total sampling that made all inpatient installation nurses totaling 77 as respondents. The data collection technique uses a questionnaire, and the analysis method uses the three box method and PLS-SEM analysis with the help of the Smart-PLS program. The results of the analysis prove that work motivation is able to positively intervene in the influence of work life quality and clinical competence on patient safety culture, so that with the role of work motivation intervention, the quality of work life and clinical competence have a greater influence in improving patient safety culture. The quality of work life and clinical competence have a positive and significant effect on work motivation and patient safety culture, and work motivation has a positive and significant effect on patient safety culture.